A ruthenium nitrosyl complex-based highly selective colorimetric sensor for biological H2S and H2S–NO cross-talk regulated release of NO. Issue 3 (20th December 2022) - Sharma, Nancy; Kumar, Vinod; Jose, D. Amilan
Abstract : A ruthenium nitrosyl complex (1·NO ) and 1·NO incorporated phospholipid-based liposomes (Lip-1·NO ) were reported for highly selective colorimetric detection of H2 S. The probe 1·NO selectively "cross-talks" with H2 S and releases nitric oxide (NO) in the process. Abstract : A ruthenium nitrosyl complex (1·NO ) and 1·NO incorporated phospholipid-based liposomes (Lip-1·NO ) were reported for highly selective colorimetric detection of H2 S. The probe 1·NO "cross-talks" with H2 S and releases nitric oxide (NO) in the process. The detection limit for H2 S was found to be 0.31 μM and 0.45 μM in the cases of 1·NO and Lip-1·NO, respectively. The DAF-FM DA assay has been performed to confirm the H2 S-induced NO release from 1·NO and Lip-1·NO . The sensing of H2 S was also verified by ESI-MS and FT-IR spectroscopy. It was also observed that external stimuli, H2 S and light worked in an almost similar way to release NO as observed by UV-Vis spectroscopy. A molecular logic gate operation "OR" was applied to the probe 1·NO in combination with inputs 'light' and 'H2 S' to give the output 'NO release'. Hence, the probe 1·NO performs the dual work of sensing H2 S with a colorimetric response, releasing NO upon cross-talk between NO and H2 S.